ORGANIZATIONAL FORMS OF ACTIVITY OF AVERAGE MEDICAL STAFF’S REHABILITATION DEPARTMENTS - Zh. A. Rizaev; Zh.Kh. Kodirov; Yoldosheva Royla Jumayevna (Journals Park Publishing, 2023)
The increase in the population's need for hospital rehabilitation care and the reform of nursing require a significant change in the functions and organization of work of nursing staff, which will contribute to a more rational use of the potential of medical workers. Expanding the powers of a nurse, increasing the prestige of this profession, a modern approach to the process of providing nursing care to a patient - all this requires the introduction of new forms of organizing the work of nurses [1,3,4].
Keywords: nursing, rehabilitation, hospitals, medical care, population.